Criticism As A Resistance Strategy in Fārūq Juwaidah’s Poems - Zulfa Purnamawati (Arabic Literature Department, 2021)
This study aims to reveal the resistance strategy used by Faruq Juwaidah, an Egyptian poet who has high concern for the fate of the Palestinians who are under Israeli Zionist rule. The object of this research material is Risalatun Ila Sarun I and II in which there are resistance values. The method used is a semiotic reading which consists of heuristic and hermeneutic reading. The results of this study indicate that the resistance strategy in Faruq Juwaidah's poetry is criticism. This form of criticism is expressed in characterization which in psychological terms is called labeling. In this term used tasybīh and isti'ārah, which are the likeness of a pig, dog and cobra. In addition, criticism is also carried out by directly pinning negative traits, such as qabīh